FORMATION OF STUDENTS' VALUE ATTITUDE TOWARDS THEIR OWN LIFE 3 PERSONALITIES OF PHYSICAL CULTURE (Physical Culture and Sport: Scientific Perspective, 2023)
In the article, the main attention is focused on the problem of the impact of the value attitude of student youth on their own health and the education of internal motivation, and especially on the formation of a high level of health culture. Emphasis is placed on the creation of a positive educational environment, which affects the formation of the value attitude of students of physical education faculties towards the culture of health. This is primarily related to the crisis in the national system of physical education of the population, which does not meet modern requirements and international standards of human physical fitness. The main causes of the crisis are the devaluation of the social prestige of health, physical culture and sports, lagging behind the modern requirements of all stages of training and retraining of physical education personnel.The strategic goal of physical education of student youth should be the formation of their physical, moral and mental health, the perceived need for physical improvement, the development of interest and habits in independent physical education and sports, the acquisition of knowledge and skills of a healthy lifestyle.One of the main features of a person is an active attitude to the surrounding world, and the forms of manifestation of this activity are very diverse. This is a wide range of actions, actions of the individual. The common basis that unites all types of an individual's active attitude to real activity is that human actions do not arise spontaneously. This is a complex social, psychophysiological process that has a specific basis. The formative and guiding basis of any activity is a motive that prompts action, a deed. Changes in students' motor activity can occur under the influence of various factors that increase or decrease the effectiveness of the educational process, the attitude of young people to physical education. One of the main such factors is the lack of free time.It was found that purposeful motivation and an appropriate educational environment are needed to change the perceived value attitude of students towards the culture of health.
Keywords: culture of health; future teachers of physical culture; value attitude; internal motivation; principle of value orientation of students; educational environment